2015
DOI: 10.1002/art.39295
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Natural Killer Cell Cytotoxicity by Interleukin‐6: Implications for the Pathogenesis of Macrophage Activation Syndrome

Abstract: Objective Systemic juvenile idiopathic arthritis (JIA) is associated with high levels of interleukin‐6 (IL‐6) in the serum and synovial fluid, and impairment of natural killer (NK) cell function is often observed. This study was undertaken to evaluate a possible link between these 2 biologic findings and whether they may be associated with the development of macrophage activation syndrome, a condition frequently observed in systemic JIA. Methods Splenocytes from wild‐type (WT) or IL‐6–transgenic (Tg) mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
189
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(208 citation statements)
references
References 51 publications
6
189
1
3
Order By: Relevance
“…In that study, no significant differences in NK cell expression of CD69 or CD107a were observed between IL-6 transgenic, and wild-type mice. However, perforin and granzyme expression in NK cells was reduced in IL-6 transgenic mice compared with that in wild-type mice (36). Therefore, it may be assumed that NK cell activity is inhibited by IL-6; however, in the present study, the IL-6R Ab did not affect NK cell numbers or maturation, and did not promote cancer metastasis in the lung metastasis mouse model.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In that study, no significant differences in NK cell expression of CD69 or CD107a were observed between IL-6 transgenic, and wild-type mice. However, perforin and granzyme expression in NK cells was reduced in IL-6 transgenic mice compared with that in wild-type mice (36). Therefore, it may be assumed that NK cell activity is inhibited by IL-6; however, in the present study, the IL-6R Ab did not affect NK cell numbers or maturation, and did not promote cancer metastasis in the lung metastasis mouse model.…”
Section: Discussioncontrasting
confidence: 64%
“…These same signaling pathways serve to maintain cell progression towards neoplastic growth, protecting cells from apoptotic death (35). With regards to NK cell activity, a previous study reported that human NK cells exposed to IL-6 exhibited reduced perforin and granzyme-B expression, which was recovered in the presence of the anti-human IL-6R Ab tocilizumab (36). In that study, no significant differences in NK cell expression of CD69 or CD107a were observed between IL-6 transgenic, and wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…Perforin and granzyme B expression of NK cells was reduced in IL6-overexpressing mice, resulting in defective cytotoxicity. Treatment of human NK cells with tocilizumab, an anti-IL6 antibody, increased perforin and granzyme B expression, enhancing their cytotoxic capacity (Cifaldi et al, 2015).…”
Section: Pathogenesis Of Secondary Hlhmentioning
confidence: 99%
“…Constitutively high IL6 expression excessively amplified the inflammatory response to Poly(I:C), CpG, lipoteichoic acid and lipopolysaccharide, the latter inducing fulminant HLH. Thus, prolonged exposure to IL6, as observed in different autoimmune and autoinflammatory diseases, not only impairs NK cell cytotoxicity but also derails the immune system towards hyperinflammatory responses (Strippoli et al, 2012;Cifaldi et al, 2015).…”
Section: Pathogenesis Of Secondary Hlhmentioning
confidence: 99%
“…Thus, IL-32a is added to the list of other cytokines that inhibit NK cell functions. For example, IL-6 has been shown to antagonize NK cytotoxicity by reducing granzyme B and perforin in the systemic juvenile idiopathic arthritis murine model, and its presence in patient sera was correlated with lower NK activity (58). TGF-b is known to reduce NK cell function by repressing the mTor pathway (59) and downregulating NKG2D or DAP10 expression, leading to an impaired cytotoxic activity of human NK cells (44,60).…”
Section: Discussionmentioning
confidence: 99%